Sudan : Staff; Monitored Program for 2009-10. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses the staff-monitored program (SMP) for 2009-10 for Sudan. Sudan's limited access to foreign financing means that significant adjustments in imports and expenditures are inevitable. The objectives of the new 18-month SMP (July 2009-December 2010) are to maintain macroeconomic stability and safeguard and rebuild foreign exchange reserves. The discussions on the SMP have focused mainly on crisis prevention. IMF staff recommends that fiscal policy of Sudan should be significantly tightened. The level of nonconcessional borrowing also needs to be carefully monitored.